2018
DOI: 10.1016/j.electacta.2017.11.074
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric supercapacitor based on vanadium disulfide nanosheets as a cathode and carbonized iron cations adsorbed onto polyaniline as an anode

Abstract: Highlights• VS 2 nanosheets electrode material was synthesized by the hydrothermal method.• C-Fe/PANI was synthesized on nickel foam by pyrolysis of the iron-PANI mixture.• The device was fabricated using VS 2 as a cathode and C-Fe/PANI as an anode.• VS 2 //C-Fe/PANI asymmetric device exhibited good electrochemical performance.ABSTRACT VS 2 nanosheets electrode material was successfully synthesized by the hydrothermal method, and the electrode material (C-Fe/PANI) based on the carbonization of Fe cations adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 58 publications
1
36
0
Order By: Relevance
“…Many literature reports can be found which demonstrate the fabrication of asymmetric supercapacitors by using either two different TMDs or a TMD with another material (popularly carbon-based). [47,48] Though different TMDs like MoS 2 , VS 2 , WS 2 , and MoSe 2 have been frequently used to fabricate an asymmetric device, MoS 2 remains the most researched material for energy storage. [49] In 2016 Yang et al [48] demonstrated an asymmetric supercapacitor with MnO 2 and MoS 2 flower-like growth on Graphene Nanosheets (GNS) as the positive and negative electrodes, respectively.…”
Section: D Tmd Electrodes For Asymmetric Supercapacitorsmentioning
confidence: 99%
“…Many literature reports can be found which demonstrate the fabrication of asymmetric supercapacitors by using either two different TMDs or a TMD with another material (popularly carbon-based). [47,48] Though different TMDs like MoS 2 , VS 2 , WS 2 , and MoSe 2 have been frequently used to fabricate an asymmetric device, MoS 2 remains the most researched material for energy storage. [49] In 2016 Yang et al [48] demonstrated an asymmetric supercapacitor with MnO 2 and MoS 2 flower-like growth on Graphene Nanosheets (GNS) as the positive and negative electrodes, respectively.…”
Section: D Tmd Electrodes For Asymmetric Supercapacitorsmentioning
confidence: 99%
“…[ 58 ] Energy density of 117 Wh kg −1 at 20.65 kW kg −1 for the vanadium sulfide‐graphene hybrids is reported whereas the value was 19 Wh kg −1 at 6 W kg −1 for bare VS 2 nanosheets. Supercapacitive performance of an asymmetric device with VS 2 nanosheets as the positive electrode and C–Fe/PANI as a negative electrode was characterized further by Rantho et al [ 117 ] The asymmetric VS 2 //C–Fe/PANI device found to be perform at a high potential up to 1.7 V in 6 m KOH with energy density of 27 Wh kg −1 at 2991.5 W kg −1 and 95% capacity retention after 10 000 cycles. VS 2 nanosheet‐based microsupercapacitors is reported to show a high specific capacitance of 4760 mF cm −2 with negligible deterioration of capacitance after 1000 cycles.…”
Section: Advanced Applications Of Vx2mentioning
confidence: 99%
“…Additional hybrid CPs with metal/metal oxides as pseudocapacitive materials for SCs are also very promising. Rantho et al successfully synthesized an asymmetric SC using VS 2 nanosheets as a cathode and carbonized iron cations adsorbed on polyaniline (C-Fe/PANI) as an anode [ 152 ]. Using 6 M KOH as an electrolyte, they evaluated the electrochemical behavior of the working electrode in a three-electrode system.…”
Section: Advanced Electrodes For Scs: Present Status and Prospectsmentioning
confidence: 99%
“…However, the results revealed that the composites had a better current response in 6 M KOH electrolyte, and the relevant explanation for such an observation was also suggested by Rantho et al They reported the specific capacitance of 516.5 F/g for VS 2 and 486.5 F/g for C-Fe/PANI. To further explore the electrochemical performance of VS 2 and C-Fe/PANI electrodes, an asymmetric device was constructed by Rantho et al The VS 2 /C-Fe/PANI asymmetric device offered a high-energy-density of 27.8 Wh/kg and a power density of 2991.5 W/kg at a current density of 2 A/g, as discussed in details elsewhere [ 152 ].…”
Section: Advanced Electrodes For Scs: Present Status and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation